Impact of lactic acid fermentation on the antibacterial activity of Curcuma longa (turmeric) against selected pathogenic bacteria - Ricasata, Chloe Katryn C.; Carigaba, Diane Ira S.
Curcuma longa, more commonly known as turmeric or luyang dilaw in the Philippines, is a tropical perennial herb widely cultivated across Asia. It is widely known for its various bioactivities such as antioxidant, anti-inflammatory, and antimicrobial properties. Recent studies have demonstrated the potential of lactic acid bacteria (LAB) fermentation to enhance the bioactive compounds in natural products. This study evaluated the effect of fermentation with Limosilactobacillus fermentum FM7 on the antibacterial activity of turmeric extract against Escherichia coli and Staphylococcus aureus. Turmeric extracts were fermented with L. fermentum FM7 and assessed alongside unfermented counterparts using agar well diffusion and broth microdilution methods. Compositional changes and antibacterial activities of fermented turmeric components were assessed using thin-layer chromatography (TLC) and TLC-contact bioautography, respectively. Results showed that fermentation led to notable antibacterial activity against both E. coli and S. aureus. The fermented turmeric extract produced zones of inhibition of 8.00 ± 1.00 diameter against E. coli, whereas no inhibition was observed for the unfermented turmeric extract. Against S. aureus, the fermented turmeric extract exhibited zones of inhibition of 10.67 ± 2.08 diameter. All measurements excluded the diameter of the wells. Moreover, the minimum inhibitory concentrations (MIC) of the fermented turmeric extract against E. coli and S. aureus were both 25 mg/mL, whereas the MIC of the unfermented turmeric extract against E. coli and S. aureus were >100 mg/mL and 25 mg/mL, respectively. TLC analysis revealed the absence of curcuminoid spots in the fermented extract, indicating possible metabolic conversion during fermentation. However, TLC-contact bioautography failed to detect specific antibacterial compounds, likely due to methodological limitations. Thus, purification of the crude extract is recommended for future studies. Overall, the findings of the study highlight the potential of LAB fermentation to enhance the antibacterial properties of turmeric and contribute to the development of alternative therapies to address AMR.